QUALITY CHARACTERIZATION OF MADHUYASHTI GHRITA (International Journal of Ayurveda and Pharma Research, 2020)
Madhuyashti Ghrita, is an Ayurvedic medicated ghee preparation containing Yashtimadhu. It is used for treating external ulcers and wounds in vital points of the body. However, there is no quality monograph available for Madhuyashti Ghrita. Hence, the present work was carried out to characterize this Ghrita to confirm its identity, quality and purity. This work reported various pharmacognostic and physicochemical parameters of Madhuyashti Ghrita along with its TLC based rapid fingerprinting as per the present standards of Ayurvedic Pharmacopoeia of India. Moreover, the presence of toxic contaminants like heavy metals, and microbial load were also evaluated. In organoleptic evaluation, the Ghrita was found to be semi–solid and dark yellow in colour, sweet and bitter in taste with a characteristic and pleasant odour. The values of the physicochemical parameters such as acid value, saponification value, peroxide value, refractive index, rancidity and pH value of the Ghrita were also assed. In the microscopical analysis of the rhizomes of Yashtimadhu, the presence of pitted vessels, fibres, prismatic crystals and starch grains were noted as a confirmation characteristic for the genuinely of this raw material in Madhuyashti Ghrita. The amount of heavy metals such arsenic, lead, mercury, cadmium, nickel, zinc, copper and chromium as well as total bacterial count and total fungal count were found to be much below their API limits. The TLC showed different characteristic spots indicating the presence of Yashtimadhu in this product. The parameters of Madhuyashti Ghrita presented in this paper may be utilized for preparing a quality monograph for this product.